The «polladas»: a survival strategy in times of economic and political crisis. Lima, 1980-2003 - Béjar Rivera, Héctor (2010)
This article describes the origin of the meetings of migrants in the slums of Lima known as «polladas» and the role they play in the survival of the families of these neighborhoods in a context of economic crisis, unemployment and underemployment. It links this practice with the traditions of reciprocal exchange and solidarity of the Andean peoples of emigration and ends by analyzing how the same practice has been implemented by the families of the middle and upper classes, but this time naming the meetings as «chicken party», in English language